An unwritten anatomy lesson: The influence of Roman clothing on neuroanatomical terminology: In memoriam Albert L. Rhoton, Jr. (1932–2016). Issue 6 (19th May 2016) - Turliuc, Dana Mihaela; Turliuc, Serban; Cucu, Andrei Ionut; Sava, Anca; Dumitrescu, Gabriela Florenta; Cărăuleanu, Alexandru; Buzdugă, Cătălin; Trandafir, Daniela; Costea, Claudia Florida
Abstract : Throughout the centuries, anatomists attempting to denominate the new structures they discovered have found inspiration in the civilization of ancient Rome and the clothing worn by its citizens. This aricle presents the origins of seven neuroanatomical terms, fimbria, velum, funiculus, lemniscus, corona, splenium, and cingulum, inspired by the clothing and jewellery of Roman women and the military attire of Roman soldiers. Thus, through their apparel, the Romans influenced the Terminologia Anatomica and "clothed" the structures of the brain and spinal cord, making them immortal. Clin. Anat. 29:685–690, 2016. © 2016 Wiley Periodicals, Inc.